From mission definition to implementation: Conceptualizing mission-oriented policies as a multi-stage translation process - Florian Wittmann; Miriam Hufnagl; Florian Roth; Merve Yorulmaz; Ralf Lindner (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
The promise of mission-oriented innovation policies (MOIP) to address some of the grand societal challenges as a cross-sectoral and interdisciplinary approach to innova-tion policy with increased directionality has raised high hopes. However, the complexity attached to MOIP constitutes a challenge, both for policy-makers and innovation schol-ars. Seeking to enhance our understanding of MOIP and the diverse policy choices and challenges involved, we propose a conceptualization of missions as multiple, intercon-nected translation processes that span from a societal challenge as the starting point to impacts as the ultimate translational stage. We argue that adopting a process-oriented perspective is well-suited to account for the interdependencies and complex feedback dynamics among the different stages during the realization of MOIP. The proposed framework aims to support the development of frameworks for impact assessment, but also yields relevant insights for policy-makers implementing MOIP.
urn:nbn:de:0011-n-6430496
Keywords: 330